(2E)-N `-Benzoyl-3-(4-nitrophenyl)prop-2-enohydrazide - Carvalho, S.A.; da Silva, E.F.; de Souza, M.V.N.; Tiekink, E.R.T.; Wardell, J.L.; Wardell, S.M.S.V. (International Union of Crystallography, 2010)
In the title compound, C(16)H(13)N(3)O(4), the dihedral angle between the terminal benzene rings is 14.02 (7)degrees. The carbonyl groups are anti with respect to each other, which facilitates their participation in the formation of supramolecular chains. Each side of the -C(=O)N(H)N(H)C(=O)- residue associates with a centrosymmetrically related molecule, resulting in the formation of essentially flat ten-membered {center dot center dot center dot O=CNN(H)}(2) synthons. The resultant chains are further consolidated in the crystal structure via C-H center dot center dot center dot O contacts.